(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The present study was carried out from selected areas at Rajshahi district to evaluate the reproductive performance of dairy cows in relation to breed/genotype, age, parity, body weight and body condition. A total of 500 cows selected and data were collected directly from the dairy farms owner by using pre-tested questionnaires during the period from September 2013 to December 2014. The average reproductive performance (RP) were recorded as age at puberty (AP) 26.42±0.22 m, age at first calving (AFC) 35.48±0.22 m, post-partum heat period (PPHP) 121.85±3.48 days, service per conception (S/C) 1.93±0.04, days open (DO) 136.80±3.57 days and calving interval (CI) 401.04±3.94 days. Genotype had significant effect (P<0.05) on all the reproductive traits except on S/C. Local (L) × Holstein Friesian (HF) genotype showed earlier AP and AFC than L× Sahiwal (SL) and L. Age group had significant (P<0.05) effect on AP, AFC and other parameters were not significant (P>0.05). Middle age groups of cows had shown better RP than others groups. Parities of cows had significant effect (P<0.05) on PPHP, S/C, DO except on AP, AFC and CI. Third parity had better RP than others. The best RP was found in >300 kg BW groups. Body condition score had significant effect (P<0.05) on all RP. Good body condition score (BCS) had excellent RP. Res. Agric., Livest. Fish.7(3): 481-495, December 2020